2009
DOI: 10.1111/j.1095-8649.2009.02442.x
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive parasitism: male and female responses to conspecific and heterospecific intrusions at spawning in a mouth‐brooding cichlid Ophthalmotilapia ventralis

Abstract: A rare form of alternative reproductive behaviour without simultaneous parasitic spawning was observed in Ophthalmotilapia ventralis, a lekking mouth-brooding cichlid from Lake Tanganyika. Floater males attempted to sneak opportunistically into the territory to actively court the female, while the owner (bourgeois male) defended the territory against other potential intruders. Floater males had more body fat than territory owners and generally higher condition factors. In field experiments, the response of bou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…We categorized 28 mouth‐brooding cichlids into four groups according to whether they built bowers or had egg‐spots or egg‐dummies (Table ): (1) bower‐building species with egg‐spots or egg‐dummies (BBE, two species), (2) bower‐building species with no egg‐spots or egg‐dummies (BBNE, seven species), (3) non‐bower‐building species with egg‐spots (NBBE, 11 species) and (4) non‐bower‐building species with no egg‐spots (NBBNE, eight species). Prior reports have shown that these cichlids have different mating systems (Table ; Ochi, ; Egger et al ., ; Schaedelin & Taborsky, ; Haesler et al ., ; Immler & Taborsky, ; Sefc et al ., ; Haesler et al ., ; Sefc et al ., ), suggesting that sperm competition levels also differ among mouth‐brooders with different mating systems.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We categorized 28 mouth‐brooding cichlids into four groups according to whether they built bowers or had egg‐spots or egg‐dummies (Table ): (1) bower‐building species with egg‐spots or egg‐dummies (BBE, two species), (2) bower‐building species with no egg‐spots or egg‐dummies (BBNE, seven species), (3) non‐bower‐building species with egg‐spots (NBBE, 11 species) and (4) non‐bower‐building species with no egg‐spots (NBBNE, eight species). Prior reports have shown that these cichlids have different mating systems (Table ; Ochi, ; Egger et al ., ; Schaedelin & Taborsky, ; Haesler et al ., ; Immler & Taborsky, ; Sefc et al ., ; Haesler et al ., ; Sefc et al ., ), suggesting that sperm competition levels also differ among mouth‐brooders with different mating systems.…”
Section: Methodsmentioning
confidence: 99%
“… 1: Kuwamura, ; 2: Schaedelin & Taborsky, ; 3: Immler & Taborsky, ; 4: Haesler et al ., ; 5: Haesler et al ., ; 6: Sefc et al ., ; 7: Egger et al ., ; 8: Sefc et al ., ; 9: Sefc et al ., ; 10: Ochi, . …”
Section: Methodsmentioning
confidence: 99%
“…ARTs are prevalent and diversified in the Lake Tanganyika cichlid tribe Lamprologini [19], although such ARTs can also be found in other Lake Tanganyika tribes ([20] and references therein). In the Lamprologini, ARTs are typically dichotomous, that is, bourgeois territorial and parasitic “sneaky” tactics (e.g., cooperative brooders, Julidochromis ornatus [21], Julidochromis transcriptus [22, 23], and Neolamprologus pulcher [24]; a shell brooder, Lamprologus callipterus [3, 25–27]; a rock-hole brooder, Telmatochromis temporalis [28]).…”
Section: Introductionmentioning
confidence: 99%
“…A female Pseudosimochromis curvifrons was seen visiting and courting with two males, but no spawning occurred on this occasion [91]. Intrusions by neighboring territory owners and attempts of parasitic spawning may also cause a female to interrupt spawning with her current mate and perhaps later resume spawning with a different male, as observed in, for example, Gnathochromis pfefferi [92] and Ophthalmotilapia ventralis [93]. In contrast, females of another open-water spawner, Cyprichromis microlepidotus , were observed to spawn their entire clutch with one male [87], and several of the genetically analyzed broods of Ctenochromis horei (43%) [85] and Simochromis pleurospilus (65%) [86] were in fact sired by a single male each.…”
Section: Substrate Breeding and Mouthbroodingmentioning
confidence: 99%
“…Quite frequently, floater males were observed to sneak into the territory and court the female, when the bourgeois male was temporarily absent chasing off other males. The small body size and good body condition of floaters suggested that floating (and sneaking) represented a transitional stage on the way to territoriality although males might also switch back and forth between the two behaviors [93]. …”
Section: Sneakers Satellites and Other Parasitesmentioning
confidence: 99%